Discrimination Abilities and Parasitism Success of Pupal Parasitoids Towards Spotted-Wing Drosophila Pupae Previously Parasitized by the Larval Parasitoid Ganaspis brasiliensis (Hymenoptera: Figitidae). Issue 6 (31st October 2022) - Hougardy, Evelyne; Hogg, Brian N; Wang, Xingeng; Daane, Kent M
Abstract: Pachycrepoideus vindemiae (Rondani) (Hymenoptera: Pteromalidae) and Trichopria drosophilae (Perkins) (Hymenoptera: Diapriidae) are two cosmopolitan and generalist pupal parasitoids that are among a few of the resident parasitoids in North America capable of attacking Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), an invasive pest of small and soft fruit crops worldwide. Ganaspis brasiliensis (Ihering) is a specialist larval parasitoid of D. suzukii that was recently approved for biological control introduction against D. suzukii in the USA. As a solitary koinobiont species, G. brasiliensis oviposits in the host larva but emerges as an adult from the host puparium. This study investigated the discrimination ability and parasitism success by the pupal parasitoids towards D. suzukii pupae previously parasitized by G. brasiliensis, to examine whether interactions with resident parasitoids will affect G. brasiliensis after it is released in the USA. We found preliminary evidence that neither pupal parasitoid could discriminate towards D. suzukii pupae parasitized by early instars of G. brasiliensis. Pachycrepoideus vindemiae was able to successfully develop on D. suzukii pupae containing all preimaginal stages of G. brasiliensis, although parasitism success was significantly higher on those bearing later rather than early stages of G. brasiliensis . Trichopria drosophilae was only able to successfully develop on D. suzukii puparia containing early instars of G. brasiliensis . These results suggest that D. suzukii parasitized by the larval parasitoid could be subsequently attacked by the pupal parasitoids, possibly affecting the success of G. brasiliensis releases.